IMPACT OF A SINGLE TUTORIAL SESSION ON THE TECHNIQUE OF USING PERSONAL PROTECTIVE EQUIPMENT BY HEALTH CARE WORKERS - Khan, Jamal Azfar; Ali, Asif; Muneer, Farzana (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the impact of a single tutorial session on the technique of donning and doffing the personal protective equipment by health care workers.Study Design: Cross-sectional comparative study.Place and Duration of Study: CMH Landi Kotal Cantt, from 1st March 2020 to 10th June 2020.Patients and Methods: The study was conducted on 62 health workers, working in CMH Landi Kotal Cantt. They were asked to demonstrate donning and doffing surgical masks, gowns and gloves and the steps were evaluated as per a standardized checklist. Then, the participants were given a single tutorial of the donning and doffing technique of personal protective equipment. They were asked to demonstrate their technique of personal protective equipment use one week, one month and three months after the tutorial. Any improvement was recorded in the checklist used earlier.Results: The correct donning and doffing technique of personal protective equipment were demonstrated by 22 and 14 participants respectively before the tutorial. When evaluated one week after the tutorial, this number increased to 48 and 38 respectively, showing significant improvement (p